Effects of ABO blood groups and RH-factor on COVID-19 transmission, course and outcome: A review - Abuawwad, Mohammad T.; Taha, Mohammad J. J.; Abu-Ismail, Luai; Alrubasy, Warda A.; Sameer, Shams Khalid; Abuawwad, Ibrahim T.; Al-Bustanji, Yaqeen; Nashwan, Abdulqadir J. (Frontiers in Medicine, 2023)
ABO and Rh blood grouping systems are two of the non-modifiable risk factors that play an important role in the susceptibility, severity and outcomes of COVID-19 infection. This review explores these associations all over the world, in an attempt to conclude a clear idea for future reference in clinical practice. In the present review, a link has been drawn between blood groups and COVID-19 transmission, course and prognosis, as literature suggests that blood group O plays a protective role against the infection, while blood group A exhibits a higher risk of exacerbation. In contrast with Rh negative individuals, Rh positive individuals are prone to more severe infection and complications, despite the fact that the underlying mechanisms of this association remain understudied. Nevertheless, the connection remains subject to controversy; since some studies report doubts about it. Thus, this association requires further investigation.